2022
DOI: 10.1007/s13178-022-00688-w
|View full text |Cite
|
Sign up to set email alerts
|

Iranian Nurses’ Experiences with Sexual Harassment in Workplace: a Qualitative Study

Abstract: Background Sexual harassment has become a worldwide issue in recent years. Nursing, like other professions, is vulnerable to this type of harm. Sexual harassment impairs nurses’ ability to provide comprehensive care, resulting in psychological discomfort, diminished work commitment, absenteeism, and job termination. The current study was carried out to investigate Iranian nurses’ experiences with sexual harassment in the workplace. Materials and Methods This qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
0
16
0
6
Order By: Relevance
“…Previous studies [21,22] have shown that nurses' implicit absenteeism is closely associated with patient falls, more medication errors and lower quality of care. In addition, persistent absenteeism may trigger the deterioration of nurses' own health, leading to more negative impacts such as impaired health productivity and economic loss [23,24]. Therefore, nurse managers should pay more attention to the needs and pressures of nurses to ensure the quality and safety of nursing through various interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [21,22] have shown that nurses' implicit absenteeism is closely associated with patient falls, more medication errors and lower quality of care. In addition, persistent absenteeism may trigger the deterioration of nurses' own health, leading to more negative impacts such as impaired health productivity and economic loss [23,24]. Therefore, nurse managers should pay more attention to the needs and pressures of nurses to ensure the quality and safety of nursing through various interventions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that at work, nurses are perceived as merely serving staff who obeyed doctor's instructions [34]. Nurses, despite being numerically superior, face challenges in rights, respect, health and comfort in clinical setting [23,35]. In order to improve the professional status of nurses and create good working conditions for nurses and provide them with all-round support, it is necessary to start from the perspective of management [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Sexual harassment in the nursing system is an acute condition that has been experienced by some nurses in various ways in the workplace ( Zeighami et al, 2022 ). Unwelcome sexual advances, behaviors, and other verbal or physical conduct of a sexual nature constitute sexual harassment when this conduct violates an individual’s dignity and creates an intimidating, hostile, degrading, humiliating, or offensive environment ( NFA, 2016 ; Danielsen and Dfaapa, 2018 ).…”
Section: Introductionunclassified
“…Sexual harassment in the nursing system is divided into five categories: verbal, physical, visual, seductive, and cyberbullying. However, patients and their families, doctors, colleagues, and other hospital staff may harass a nurse ( Zeighami et al, 2022 ). According to a survey of Danish employees, the prevalence of sexual harassment was 3.1% across all occupations, but 16.4% among healthcare workers ( NFA, 2016 ).…”
Section: Introductionunclassified
See 1 more Smart Citation